2006
DOI: 10.1242/dev.02612
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic dynamics of theKcnq1imprinted domain in the early embryo

Abstract: The mouse Kcnq1 imprinted domain is located on distal chromosome 7 and contains several imprinted genes that are paternally repressed. Repression of these genes is regulated by a non-coding antisense transcript, Kcnq1ot1, which is paternally expressed. Maternal repression of Kcnq1ot1 is controlled by DNA methylation originating in the oocyte. Some genes in the region are imprinted only in the placenta, whereas others are imprinted in both extra-embryonic and embryonic lineages. Here, we show that Kcnq1ot1 is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
77
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 41 publications
(60 reference statements)
9
77
1
Order By: Relevance
“…Three other putative imprinted genes, SCL22A18, PHLDA2 , and KCNQ1 , are located on chromosome 21 (Figure 6) in the KCNQ1 domain, which contains several maternally expressed genes [48,49]. In our analysis, these three ovine genes also showed preferential expression from the maternal allele.…”
Section: Discussionmentioning
confidence: 51%
“…Three other putative imprinted genes, SCL22A18, PHLDA2 , and KCNQ1 , are located on chromosome 21 (Figure 6) in the KCNQ1 domain, which contains several maternally expressed genes [48,49]. In our analysis, these three ovine genes also showed preferential expression from the maternal allele.…”
Section: Discussionmentioning
confidence: 51%
“…S6A) (11), which is reflected in TS and XEN cells. This contrasts, however, with postimplantation stage extraembryonic tissues, where we detected high gene-specific Kcnq1ot1 is used as a positive control (46). Mean and SD are from two biological replicates.…”
Section: Discussionmentioning
confidence: 64%
“…This would be analogous to de novo DNA methylation that occurs during preimplantation development (45). In support of this hypothesis, placentally imprinted genes acquire their differential histone marks in trophoblast between E4.5 and E7.5, and TS cells display a set of epigenetic marks before this event (46). An alternative explanation is that although global H3K27me3 is low in the extraembryonic lineages before implantation, there may still be genes marked by H3K27me3 in these tissues and these marks persist after implantation.…”
Section: Discussionmentioning
confidence: 78%
“…Interesting parallels can be drawn between our findings and those of imprinted clusters in which sequential and lineage-specific gene silencing linked to noncoding RNAs, such as Kcnq1ot1, have been reported. In the Kcnq1-imprinted cluster the Kcnq1ot1 RNA is paternally expressed at the 2-cell stage and is believed to participate in silencing of flanking genes on the paternal chromosome (22). It has been suggested that Kcnq1ot1 RNA represses its most proximal genes in all cells (both embryonic and extraembryonic) but that silencing spreads to more distant genes only in the trophoblast, after implantation.…”
Section: Discussionmentioning
confidence: 99%